2021
DOI: 10.1155/2021/9987646
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Glucose Monitoring in Women with Normal OGTT in Pregnancy

Abstract: Continuous glucose monitoring (CGM) might be an effective tool to improve glycemic control in gestational diabetes mellitus (GDM). Few data are available about its utilization as a diagnostic tool to find potential alterations of glycemia in subjects with normal oral glucose tolerance test (OGTT). In this preliminary prospective real-life observational study, we aimed to analyze the glycemic pattern in normal and gestational diabetes mellitus (GDM) women by continuous glucose monitoring (CGM) in order to detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 42 publications
2
15
0
Order By: Relevance
“…A more recent study from Tartaglione et al applied CGM (Medtronic iPro2) to the analysis of postprandial and fasting BGL in a cohort of 99 women seven days after the OGTT [ 47 ]. Among the 53 NGT, 33 women were found to have BGL above or below the recommended thresholds and were managed with a one week of SMBG and diet.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A more recent study from Tartaglione et al applied CGM (Medtronic iPro2) to the analysis of postprandial and fasting BGL in a cohort of 99 women seven days after the OGTT [ 47 ]. Among the 53 NGT, 33 women were found to have BGL above or below the recommended thresholds and were managed with a one week of SMBG and diet.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 53 NGT, 33 women were found to have BGL above or below the recommended thresholds and were managed with a one week of SMBG and diet. Twelve of these women ended up requiring insulin [ 47 ]. In this study no differences were found in average daily glucose, time spent in the different ranges by GDM and NGT women and maternal and fetal outcomes [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because glucose freely crosses the placenta, maternal hyperglycemia associated with GDM causes elevated glucose levels in the fetus, resulting in hyperinsulinism 40,41 . Thus, frequent monitoring and evaluation of glucose levels among delivered mothers is crucial worldwide in general and in the study area in particular to reduce the burden of hypoglycemia in neonates 42,43 . Although this study attempted to explore hypoglycemia and its associated factors for the first time in the study, it has some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of neonatal respiratory distress syndrome, neonatal pneumonia, neonatal hypoglycemia, and neonatal asphyxia is not significantly different between A1 GDM and normal pregnancies. Tartaglione et al [ 26 ] continuously monitored and adjusted blood glucose levels in 46 patients with GDM and 53 normal controls and found no differences in maternal and fetal outcomes between them when blood glucose levels were consistently controlled. Hochberg et al [ 27 ] compared the differences in maternal and fetal outcomes after induction of labor from 37-38 wk in 193 non-GDM patients and 39-40 wk in 237 singleton pregnant women with well-controlled GDM and found no differences between gestational week intervals.…”
Section: A1 Gdmmentioning
confidence: 99%